Preference, Knowledge, and Attitudes of Parents Toward Cognitive Behavioral Therapy for Their Children in Riyadh, Saudi Arabia - Alenezi, Shuliweeh; Albawardi, Ibrahim M.; Aldakhilallah, Amirah; Alnufaei, Ghaliah S.; Alshabri, Rahaf; Alhamid, Lama; Alotaiby, Alanoud; Alharbi, Norah (Frontiers in Psychology, 2021)
Introduction Cognitive-behavioral therapy (CBT) for children and adolescents has shown efficacy in treating different psychiatric disorders. It has been added to multiple clinical guidelines as the first-line treatment. However, despite mountains of evidence of its efficacy, CBT is underutilized in clinical settings due to a lack of rigorous training programs and qualified CBT therapists. Parents' limited knowledge of this intervention and their negative attitudes towards it have been considered as possible reasons. Methods This is a cross-sectional survey-based study among 464 Saudi parents living in Riyadh city. We aimed to evaluate Saudi parents' preference, knowledge, and attitudes towards CBT for their children. We compared the difference in the level of knowledge and attitudes towards CBT in relation to the characteristics of parents. An online questionnaire that included 39 questions was carefully reconstructed from four validated scales, approved by an expert panel, and piloted. Participants were recruited to participate through online social media. Results Saudi parents had average knowledge about CBT; however, they had positive attitudes toward the therapy itself and its role in treating children's behavioral issues. Male participants showed to have better knowledge than female participants. Higher education participants and those with high income have favorable attitudes toward CBT than others. Conclusion Parents' knowledge is considered inadequate and stated the need for more awareness and perhaps a mass education. On the other hand, they kept positive attitudes and were interested in evidence-based treatment with more preference towards non-psychopharmacological interventions.